(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
Gymnanthemum amygdalinum (Delile) Sch.Bip. ex Walp. (Asteraceae), better known by its former name Vernonia amygdalina Delile, is a small shrub used in folk medicine as an antipyretic, laxative, antimalarial and anthelmintic. Studies have demonstrated that different vegetal extracts possess antioxidant, antimicrobial and antiparasitic activities. Among the bioactive metabolites, there are sesquiterpene lactones, saponins, polyphenols and flavonoids. This study investigated the leaf and stem microscopic characters of G. amygdalinum, aiming to expand the knowledge on this medicinal species and indicate anatomical structures. Plant material was fixed and sectioned by freehand and using a microtome. The sections were either stained or underwent standard histochemical tests. Scanning electron microscopy was performed to investigate epidermal relief. The leaf is amphistomatic with anomocytic stomata. There are striate cuticle, glandular and non-glandular trichomes and dorsiventral mesophyll. In transverse section, the midrib and the petiole have a plano-convex shape. Both show several collateral vascular bundles and few crystals of calcium oxalate. In the stem, the epidermis persists and the phellogen has a peripheral origin. It presents typical endodermis and sclerenchymatic caps adjoining the phloem. The aspects that contribute to characterizing the species are stomata on both leaf surfaces, midrib and petiole features, the endodermis and sclerenchymatic caps in the stem, as well as the different types of trichome on both aerial organs.